Simplified MLST scheme for direct typing of Leptospira human clinical samples - Varni, Vanina Delia (2018)
Leptospirosis is a globally distributed zoonosis. Epidemiological data are scarce and present major challenge because of the varied clinical presentations. Multilocus Sequence Typing has already proven to be a robust molecular typing method providing accurate results for strain characterization. We have adapted our MLST scheme by reducing the set of loci to facilitate Leptospira typing directly from human clinical samples. The application of this 3-locus scheme provides Leptospira species and allelic profiles of the samples retaining the power of discrimination of the whole scheme. Moreover, an approach to the serogroups was also achieved. Our results contribute to the epidemiological study of Leptospirosis, since the direct typing on clinical specimens could detect and update allelic variants and serogroups present in a region. The simplified scheme allowed at the same time to take advantage of limited genetic material available in clinical samples that may increase the sources of information for epidemiological monitoring.